Dasar-Dasar Pengetahuan Tasawuf - Badani, Abd Quddus al (Lembaga Yasin AlSys, 2021)
In the teachings of Islam, the science of Sufism is an important thing to learn more about in lectures. Sufism is a process to purify oneself with the aim of knowing Allah (mak'rifat tullah). According to Al-Jurari, when asked about Sufism, he replied that Sufism is entering into all Sunnah (morals) (Ahl al sunnah wa al jama'ah) and getting out of low character. The concept in Sufism cannot be separated from the Qur'an and Hadith.